Risk Factors and Impact of Urinary Incontinence Among Menopausal Women in Sulaimani City: A Cross-Sectional Study - Karem, Nassreen Ahmad (Journal of Neonatal Surgery, 2025)
Background and Objectives: Urinary incontinence (UI) significantly affects the quality of life (QOL) in menopausal women. This study aimed to evaluate UI prevalence, and risk factors impact among menopausal women in Sulaimani City. Methods: A cross-sectional design enrolled 200 menopausal women (45–65 years) via purposive sampling. Data on socio-demographic, reproductive, and medical factors were collected through validated questionnaires. Chi-square tests and Pearson’s correlation analyzed associations between variables and UI severity. Results: The most prevalent severity of UI among women was moderate, observed in 101 (50.5%) menopausal women. This was followed by severe incontinence in 52 (16%) women, and mild incontinence in 47 (25.5%) women. There was a direct and significant relationship between age, change in employment status, social status, parity, and the number of vaginal deliveries with the types, degree, and duration of UI (P≤0.001). Conversely, there was a negative and significant relationship between increased age at marriage, increased time since hysterectomy, diabetes mellitus, urinary tract infections (UTI), and genital prolapse with the type, severity, and duration of incontinence (P ≤0.005). Conclusion: As age increased, menopausal women experienced an increase in the type, severity, and duration of incontinence. However, with increased age at marriage, longer time since hysterectomy, diabetes mellitus, UTI, and genital prolapse, the type, severity, and duration of incontinence decreased.